Evaluation of Results of Extraperiosteal Plating of Pronation-Abduction Ankle Fractures in Adults - Kabir, Tafhim Ehsan; Ahmad, Salehuddin; Biswas, Alak Kanti (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Pronation-abduction ankle fractures frequently are associated with substantial lateral comminution and is associated with the highest rates of nonunion among indirect ankle fractures. It is one of the common injuries occurring in adult age group where trauma is the main etiology. The present prospective hospital based observational study was conducted to evaluate the functional outcome of treatment of ankle fracture by extraperiosteal plating in a series of patients with pronation-abduction ankle fractures. Materials and methods : A total of 30 consecutive patients aged over 18 years with pronation-abduction ankle fracture were included in the study and underwent surgery by extraperiosteal plating of the fibular fracture. Patients were selected irrespective of sex. The average age of the patients was 36.5 years. Patients with gustilo type III open fractures, pathological fractures were excluded from the study. The patients were evaluated functionally with the use of the American Orthopaedic Foot and Ankle Society score (AOFAS) radiographically, and clinically with range of motion testing. Results: Immediate postoperative and final follow-up radiographs showed that most of the patients had a well-aligned ankle mortise on the fractured side as compared with the normal side on the basis of standardized measurements. All fractures healed without displacement. The average American Orthopaedic Foot and Ankle Society score was 81.5. The range of motion averaged 13° of dorsiflexion and 53° of plantar flexion. Satisfactory results were obtained in 93.33 % patients. Complication includes 2(6.66%) superficial infection, 1(3.33%) deep infection, 4(13.33%) delayed union, 1(3.33%) skin necrosis. Radiological evaluation revealed persistent of talar shift in 1(3.33%) patient postoperatively. Conclusions: Extraperiosteal plating to be an effective method for the stabilization of pronation-abduction ankle fractures. The technique allows for accurate reduction of the mortise without stripping the periosteum of the comminuted region of the fracture. The technique is easier and faster than standard techniques in which the lateral periosteum is split to facilitate placement of the plate. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 32-36